Jak ťuhýk obecný (Lanius collurio) rozpoznává nepřátele - Němec, Michal (Jihočeská univerzita, 2015)
This study investigates two questions about anti-predator behaviour of the red-backed shrike. 1) Is the red-backed shrike able to assess the differing dangers represented by various types or species of predators? 2) How does the red-backed shrike recognize the predator? We found, that the red-backed shrike (Lanius collurio) adjusts its anti-predator behaviour by assessing the potential threat to themselves from different predator species and by assessing the chance of a successful attack. Further, we found that the presence of general raptor salient features is absolutely necessary for proper categorisation of the intruder as a predator, whereas the natural species-specific colouration in itself is an insufficient cue.
How the red-backed shrike (Lanius collurio) recognizes enemies
Keywords: ťuhýk; predátor; antipredační chování; obrana hnízda; rozpoznání nepřítele; vetřelec; kognitivní schopnosti; atrapový experiment; shrike; predator; anti-predator behaviour; nest defence; enemy recognition; intruder; cognitive abilities; dummy experiment